2022
DOI: 10.1039/d1ce01608c
|View full text |Cite
|
Sign up to set email alerts
|

One-step fabrication of nitrogen-doped laser-induced graphene derived from melamine/polyimide for enhanced flexible supercapacitors

Abstract: Heteroatom doping of graphene electrodes is a valid strategy to enhance its capacitive performance. This work demonstrates a facile and expandable methodology to the in-situ fabrication of nitrogen-doped laser-induced graphene...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 56 publications
(66 reference statements)
0
22
0
Order By: Relevance
“…The curves both exhibit a triangular shape, suggesting their EDLC capacitance characteristics. 42 Moreover, it can also be seen that compared with PL-PCN-MSC, P–TiC-MSC exhibits a more pronounced IR-drop (the voltage drop located at the beginning of the discharge process), demonstrating the higher internal resistance of P–TiC-MSC. 43 On the basis of the GCD curves of PL-PCN-MSC and P–TiC-MSC (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The curves both exhibit a triangular shape, suggesting their EDLC capacitance characteristics. 42 Moreover, it can also be seen that compared with PL-PCN-MSC, P–TiC-MSC exhibits a more pronounced IR-drop (the voltage drop located at the beginning of the discharge process), demonstrating the higher internal resistance of P–TiC-MSC. 43 On the basis of the GCD curves of PL-PCN-MSC and P–TiC-MSC (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Remarkably, the areal energy density of PL-PCN-MSC is up to 14.73 μW h cm −2 at an areal power density of 0.05 mW cm −2 , which is obviously higher than 0.22 μW h cm −2 for 3D porous graphene, 46 0.47 μW h cm −2 for graphene quantum dots, 9 1.07 μW h cm −2 for graphene/activated carbon, 18 2.6 μW h cm −2 for laser-scribed graphene, 47 4.73 μW h cm −2 for porous graphene, 48 5.07 μW h cm −2 for N-doped porous carbon, 49 and 4.89 μW h cm −2 for N-doped graphene. 42 Finally, the cycling stability of PL-PCN-MSC was evaluated at a scan rate of 100 mV s −1 , as shown in Fig. 6j.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, through the analysis of the form of N element in different samples, when the unstable nitrogenous substance is removed, the remaining small content N element can not only further verify the influence of laser on the structure of LPC material but also improve the aggregation and accumulation between LPC layers, which helps to improve the electrical conductivity of the material. The trace N element can provide a reliable medium for charge and ion transport without affecting subsequent electrochemical tests. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, doping of heteroatoms such as nitrogen and phosphorus is also a valid strategy to modify hierarchical nanoporous carbon electrodes, which change their electron transfer characteristics and provide redox reactions. , For instance, Tour et al reported a boron-doped graphene electrode, whose performance is three times greater than that of an undoped electrode . Han et al optimized the ratio of nitrogen sources inside the carbon precursor to prepare the N-doped graphene electrode, leading to a 7.2-fold increased capacitance . However, the reasonable doping concentration of heteroatoms is difficult to control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation